Auricular Composite Grafting in Functional Rhinoplasty - Rao, Neela; Toriumi, Dean M. (Facial Plastic Surgery, 2017)
Surgical correction of defects of the internal nasal valve, ala, vestibule, and sill is widely regarded as a challenge due to concerns of poor outcomes of facial aesthetics and nasal function. Auricular composite grafting is a reliable method of reconstruction of deformities of the nasal vestibule and sill. A classification system of types of defects may help surgeons in understanding the indications for composite grafting. Furthermore, we have developed surgical techniques that enhance survival of composite grafts of larger size. Composite grafting is an effective technique to repair a wide range of defects of the internal nasal valve, nasal sill/ala, and vestibule with excellent functional and aesthetic results.
Keywords: composite graft; rhinoplasty; functional rhinoplasty; vestibular stenosis; alar retraction